(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To study the effectiveness of paravertebral block for perioperative analgesia in patients undergoing breast or gallbladder surgery. To study the effect of paravertebral block on hemodynamics and blood glucose level. Patients and Methods: Seventy female patients undergoing breast or gallbladder surgery under general anesthesia were included in the study. Thirty five patients were put in control group (A) while thirty five patients were in the study group (B). All patients underwent surgeries under general anesthesia. Group A patients received standard perioperative analgesia while group B patients were administered unilateral paravertebral block before induction while awake. Postoperative pain was evaluated in all patients using visual analog scale and compared in both groups. Mean blood pressure and pulse rates were recorded before, during and after the surgical procedure and compared between the groups. Patient’s blood glucose were also monitored during the surgical procedure and compared between the groups. Results: The mean age of group A patients was 46.33+ 11.08 and Group B was 44.33+15.6. The mean pain score was significantly higher in group A (2.6+1.72) compared with group B (1.11+1.56) (p value <0.01). Blood pressure, pulse and blood glucose levels were not significantly different between the groups in pre operative, during surgery or postoperative period. Conclusions: Paravertebral block provides better analgesia in postoperative period compared with standard postoperative care. Paravertebral block has no significant effect on blood pressure, pulse rate or blood glucose level.